Pengembangan Model Pembelajaran Lompat Jauh Berbasis Problem Based Learning Untuk Kelas VIII SMPN 2 Nganjuk - Visco Armadhani; Mu’arifin Mu’arifin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The problem-based learning (PBL) model is an approach that directs students to learn and work together to solve problems in the real world. Referring to the results of observations that researchers conducted at SMPN 2 nganjuk, still using a conventional learning model. This can be seen from the knowledge and skills of students who have not met the minimum standards set by the school. So that researchers provide solutions in the form of applying PBL-based learning models in the subject matter of long jump hanging style. This study aims to develop and test the feasibility of PBL-based long jump hanging style learning model products. This type of study is Research and Development (R&D) whose stages include conducting needs analysis, identifying learning models, developing learning models, evaluation, small group tests and large group tests. This research data collection uses instruments in the form of observations, interviews, and questionnaires. The results of the percentage calculation by 2 learning experts amounted to 97.08% and the average of the material experts was 95.00%. Furthermore, for the small group trial, 3 PJOK teachers got an average score of 92.16% and the value of 12 VIII grade students averaged 94.44%. As for the large group test on 4 PJOK teachers obtained an average of 93.75% and the value of 34 VIII grade students averaged 96.74%. So it is concluded that the product development of a PBL-based learning model for long jump hanging style material for class VIII SMP Negeri 2 Nganjuk is declared very feasible to use.